Molecular Mechanisms of Endocrine Resistance in Estrogen-Receptor-Positive Breast Cancer - Belachew, Esmael Besufikad; Sewasew, Dareskedar Tsehay (Frontiers in Endocrinology, 2021)
The estrogen receptor is a vital receptor for therapeutic targets in estrogen receptor-positive breast cancer. The main strategy for the treatment of estrogen receptor-positive breast cancers is blocking the estrogen action on estrogen receptor by endocrine therapy but restricted via the endocrine resistance. Endocrine resistance is resulted due to both de novo and acquired resistance. This review focused on the mechanisms of ligand-dependent and ligand-independent pathway and other coregulators, which are responsible for endocrine resistance. From this review, we concluded that combinatorial drugs that target different signaling pathways and coregulatory proteins together with endocrine therapy could be a novel therapeutic modality to stop endocrine resistance.